Impact of Heat Treatment on Wheat Flour Solvent Retention Capacity (SRC) Profiles. Issue 6 (20th November 2013) - Van Steertegem, Bénédicte; Pareyt, Bram; Slade, Louise; Levine, Harry; Brijs, Kristof; Delcour, Jan A.
ABSTRACT: The impact of heat treating wheat flour (for 2 or 5 h at 80 or 100°C) on its functional properties was studied with solvent retention capacity (SRC) tests and related to changes in individual groups of flour constituents. Heat treatments increased the overall water retention capacity (from 55.6% for control flour to 62.4% for flour heated 5 h at 100°C) as well as sucrose SRC (from 85.0 to 113.5%), although no changes were observed in sodium carbonate SRC. The decrease in lactic acid SRC values (from 113.1 to 97.4%) indicated that heat treatment restricted swelling of the protein network. As deduced from a decrease in both the level of proteins extractable in sodium dodecyl sulfate–containing medium and the level of free sulfhydryl groups, the restricted swelling was related to protein cross‐linking within the flour particles. Such upfront polymerization prevented proper hydration and gluten network formation during mixing. Starch (swelling) properties were also affected by heat treatment. Finally, the impact of heat treatment on flour SRC profiles was comparable to that noted when chlorinating wheat flour.